2012
DOI: 10.1177/8756479312442006
|View full text |Cite
|
Sign up to set email alerts
|

Larsen Syndrome

Abstract: Larsen syndrome is a rare inherited disorder of collagen formation with multiple joint dislocations, cardiac abnormalities, short stature, talipes equinovarus, short and broad fingertips, spatula-like thumbs, supernumerary ossification center in the calcaneus, hearing loss, neurologic impairment, cryptorchidism, and characteristic craniofacial abnormalities. The sonographic prenatal findings in a case of Larsen syndrome at 26 weeks' gestation, which demonstrated joint dislocations, hypertelorism, frontal bossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The systematic search of the literature identified 742 studies, of which 726 were excluded and 16 were included in the analysis (Figure 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Nineteen cases with a prenatal diagnosis of CKD were retrieved from the identified studies and an additional case was found in the database of our center.…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The systematic search of the literature identified 742 studies, of which 726 were excluded and 16 were included in the analysis (Figure 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Nineteen cases with a prenatal diagnosis of CKD were retrieved from the identified studies and an additional case was found in the database of our center.…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
“…Cases with Larsen syndrome presented with a flat facial profile (60%), micrognathia (100%), hypertelorism (60%), bilateral or unilateral hip dislocation (60%), short nasal bridge (40%) and low-set ears (40%). Prenatal diagnosis of Larsen syndrome was suspected following ultrasound detection of fetal abnormalities, with three cases confirmed postnatally based on clinical assessment alone by a geneticist 8,11,16 and two confirmed with the adjunct of LAR1 mutation genetic testing 14,19 . The diagnosis of Noonan syndrome was made after TOP at 17 weeks for mirror syndrome in a fetus with multiple anomalies with DNA analysis showing PTPN11 mutation 15 .…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation